ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN PT SUMMIT OTO FINANCE BRANCH OF SURABAYA - Eni Yuli Siswati; Agus Sukoco (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to determine and analyze how much influence the quality of services on the level of satisfaction felt by customers who use the financing services of PT Summit Oto Finance Surabaya Branch. The model used in this research is the method of observation, interviews, and questionnaires using a Likert scale and the method of determining the sample used is Proportionate Stratified Random Sampling of 100 samples. The analytical method used is the multiple linear regression method (Multi Linear Regression. The results of the study obtained the regression equation Y = 0.408 + 0.035X1 + 0.320X2 + 0.183X3 + 0.217X4 + 0.277X5. Where simultaneously all variables are tangible, reliability, responsiveness, assurance. , and empathy have a significant influence and positive direction of the relationship on customer satisfaction, while partially only tangible variables that do not affect customer satisfaction The most influencing variable on customer satisfaction is the variable reliability (2,898).